The Influence of Work Motivation and Work Environment on the Productivity of Health Workers at Samaritan Palu Hospital - Oswar Irfan; Rukhayati; Haris Abd. Kadir (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This study aims to analyze the effect of work motivation and work environment on the productivity of healthcare workers at Rumah Samaritan Palu Hospital. The research employed a quantitative approach using a survey method involving 149 respondents. Data were collected through questionnaires, while data analysis was conducted using multiple linear regression with the assistance of SPSS, including t-test and F-test. The results indicate that partially, work motivation has a significant effect on the productivity of healthcare workers with a t-value of -2.172 and a significance level of 0.031, but it shows a negative relationship. Meanwhile, the work environment has a significant and dominant effect on productivity with a t-value of 22.153 and a significance level of 0.000. Simultaneously, work motivation and work environment have a significant effect on the productivity of healthcare workers with an F-value of 512.703 and a significance level of 0.000. The conclusion of this study reveals that the work environment is the main factor in improving the productivity of healthcare workers, while work motivation needs to be properly managed to avoid negative impacts on productivity.